Regulatory Genetic Networks by microRNAs: Exploring Genomic Signatures in Cervical Cancer - Carlos Pérez-Plasencia; Yaneth Citlalli Orbe-Orihuela; Armando Méndez-Herrera; Jessica Deas; Claudia Gómez-Cerón; Hilda Jiménez-Wences; Julio Ortiz-Ortiz; Gloria Fernández-Tilapa; Aldo Francisco Clemente-Soto; Jesús Ricardo Parra-Unda; Jesús Salvador Velarde-Felix; Mauricio Rodríguez-Dorantes; et al. (Biomedicines, 2025)
Cervical cancer remains a significant global health concern, impacting over half a million women annually. The primary cause is a persistent infection with hr-HPV, which disrupts various cellular processes crucial for normal function. This disruption leads to genetic instability, including changes in the expression of microRNAs and their corresponding host genes, with far-reaching consequences for cellular regulation. Researchers have widely utilized high-throughput technologies to analyze gene expression in cervical cancer, aiming to identify distinct molecular signatures of microRNAs and genes through genomic analysis. However, discrepancies among studies have been noted, possibly due to variations in sample collection, technological platforms, and data processing methods such as normalization and filtering. Therefore, it is essential to synthesize findings from diverse studies to comprehensively understand the molecular mechanisms of regulatory genetic networks involved in the initiation and progression of cervical cancer. This review examined the evidence detailing the role of microRNA signatures and their target genes in cervical carcinogenesis and disease advancement. The accumulated data suggest the presence of widespread regulatory genetic networks active in both precancerous and cancerous cervical cells, potentially acting as key drivers of this malignancy. Identifying these molecular genomic signatures could open new avenues for developing therapeutic strategies for cervical cancer, particularly in the realm of precision medicine.